Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Karawang - Fara Damayanti; Suroso; Flora Patricia Angela (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of work motivation and work discipline on the performance of employees at the BPKSDM Karawang Regency. The research method used is quantitative. The study was conducted at the BPKSDM Kab. Karawang involving 53 individuals. The sampling technique used is saturation sampling. The data analysis model uses multiple linear regression. The t-test and F-test are employed with a significance level of 5%. Findings indicate that there is an influence of work motivation on the performance of employees at BPKSDM Karawan g regency, with a t-score of (4.922 > 2.008) or (t-calculated > t-table). Furthermore, there is a partial influence of work discipline on the performance of employees at BPKSDM regency Karawang, with a t-score of (2.684 > 2.008) or (t-calculated > t-table). Simultaneously, work motivation and work discipline have a positive influence on the performance of employees at BPKSDM Karawang regency.